2018
DOI: 10.1016/j.celrep.2018.07.069
|View full text |Cite
|
Sign up to set email alerts
|

Distinct HLA-E Peptide Complexes Modify Antibody-Driven Effector Functions of Adaptive NK Cells

Abstract: Adaptive NK cells are characterized by profound alterations in multiple signaling molecules, transcription factors, and epigenetic modifications compared with canonical NK cells. Although their existence is associated with prior exposure to human cytomegalovirus (HCMV), key questions regarding their regulation and function remain. A large proportion of adaptive NK cells express the activating receptor CD94/NKG2C, binding to human leukocyte antigen E (HLA-E), that presents a limited set of peptides. We show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
111
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(114 citation statements)
references
References 63 publications
3
111
0
Order By: Relevance
“…Recently it was demonstrated that HCMV-derived peptides presented by HLA-E, in particular the rare UL40 peptide VMAPRTLFL which is identical to the HLA-G leader peptide, fine tune the ADCC response of NK cells via NKG2C recognition (17). Both membrane bound and soluble levels of HLA-G are reported to be increased in untreated HIV infection and during HCMV infection and have been shown to correlate with blood IFN-γ concentrations and could therefore represent a source of HLA-E peptides in T/T individuals (29) (30) (31).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently it was demonstrated that HCMV-derived peptides presented by HLA-E, in particular the rare UL40 peptide VMAPRTLFL which is identical to the HLA-G leader peptide, fine tune the ADCC response of NK cells via NKG2C recognition (17). Both membrane bound and soluble levels of HLA-G are reported to be increased in untreated HIV infection and during HCMV infection and have been shown to correlate with blood IFN-γ concentrations and could therefore represent a source of HLA-E peptides in T/T individuals (29) (30) (31).…”
Section: Resultsmentioning
confidence: 99%
“…In keeping with this, we observed a range of ADCC responses in our cohort that correlated with NKG2C expression. Furthermore, UL40 in HCMV encodes peptides that mimic MHC class I signal sequences and share a conserved methionine (M) anchor residue at peptide amino-acid residue 2), which correspond to amino acid −21 of the classical HLA class I leader sequence (16) (17). Hence HCMV infection provides peptides that may substitute for host HLA-I-derived HLA-E stabilising nonameric peptides in T/T donors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular HCMV co-infection, a hallmark of HIV-1 infected cohorts, triggers a dramatic expansion of differentiated NK cells expressing the activating receptor NKG2C, which prototypically characterises adaptive NK cells (Guma et al, 2006) (Mela and Goodier, 2007) (Brunetta et al, 2010). These expanded NKG2C+ NK cells co-express CD57, a marker of maturation, and are influenced by HLA-E presented peptides (Hammer et al, 2018) (Rolle et al, 2018). Notably they resemble memory CD8 T cells and are imbued with enhanced capacity for antibody dependent cellular cytotoxicity (ADCC), in particular increased IFN-γ production attributed to epigenetic remodelling of the IFNG locus (Schlums et al, 2015) (Lee et al, 2015).…”
Section: Introductionmentioning
confidence: 99%